Desain Bahan Ajar Berbasis Kemampuan Koneksi Matematis Siswa SMP Pada Kelas VII - Dani Syahrul Fajar; Ika Wahyuni; Dina Pratiwi Dwi Santi (Department of Mathematics Education, Universitas Kuningan, 2019)
The background of this research is the learning obstacle on the material of the VII grade MTs algebraic operating material. This study aims to describe how the design of didactic teaching materials based on the mathematical connection ability of junior high school students in class VII. Subjects in this study were students of MTs PUI Majalengka, 28 students of class VII A to identify learning obstacles and 10 students of class VII A were used as samples for the implementation of teaching materials. The research carried out was a didactic design research consisting of three stages, namely: (1) didactic situation analysis prior to learning in the form of a Didactic Design Hypothesis including ADP, (2) methadactic analysis, and (3) retrosfective analysis. How to collect data by tests, validation of teaching materials, and student questionnaire responses. The results showed that there were three types of obstacle learning. The validation results obtained can be concluded that teaching materials based on students' mathematical connection abilities can be used in learning algebraic form operations. The implementation of this didactic design is in accordance with predictions so that the design of this teaching material can be used as an alternative design of learning algebraic operations learning.